System of prolonged psychotherapeutic support of patients with psychoendocrine syndrome on the hypocorticism background - V. V. Ischuk (Kazimierz Wielki University, 2017)
The objective: to form a nosological differentiated system of psychotherapeutic support of patients with psychoendocrine syndrome on the background of hypocorticism. The base of the research done: Ukrainian Scientific and Practical Center of Endocrine Surgery, Endocrine Organs and Tissue Transplantation of the Ministry of Health ofUkraine. 50 patients with hypocorticism were examined. Methods: clinical-psychopathological, clinical-psychophenomenological. Results: the nature and extent of the relevance of nosogenic psychotraumatic factors in the patients under examination in three chronopathological periods (early, delayed and late) were established. A system of prolonged psychotherapeutic support has been developed. It is realized by selective application of contranozogenic psychotherapeutic interventions, depending on activity of a particular factor at this stage of the disease.